Enhanced transmembrane proton conductance in Streptococcus mutans GS-5 due to ionophores and fluoride. - Eisenberg, A D (1981)
The uptake of protons by intact cells of Streptococcus mutans GS-5 was measured directly by assessing the pH increase in lightly buffered cell suspensions as protons moved across the plasma membrane after acid pulses. The barrier function of the cell membrane for protons was disrupted completely by 5% (vol/vol) butanol. This function was compromised severely by the ionophores valinomycin and gramicidin and by the uncoupler carbonylcyanide-m-chlorophenyl hydrazone. Proton conduction across the membrane was also enhanced by fluoride. It appeared that HF traversed the membrane and acted as a carrier. Once in the relatively alkaline cytoplasm, HF dissociated to yield F- and H+, which acted to acidify the cytoplasm and reduced the pH difference across the membrane.